Influence of micro end milling process parameters on surface roughness - Ali, Mohammad Yeakub; Amin, A. K. M. Nurul; Mehfuz, R.; Najran, W.; Akif, M. (2008)
This paper reports the influence of micro end milling process parameters on surface roughness of beryllium copper alloy. A number of microchannels were fabricated in order to characterize the process parameters influencing surface roughness. Two-level four-factor statistical models were developed to predict the average (Ra) and peak-to-valley (Rt) surface roughness. Experiments were conducted with four process parameters: feed rate, depth of cut, cutting speed and tool diameter. The interaction effect of parameters was studied. Both Ra and Rt were found strongly influenced by feed per tooth, depth of cut and tool diameter. An average surface roughness of 0.30 μm was observed.